2012
DOI: 10.1016/j.cell.2012.06.036
|View full text |Cite
|
Sign up to set email alerts
|

Prophage Excision Activates Listeria Competence Genes that Promote Phagosomal Escape and Virulence

Abstract: The DNA uptake competence (Com) system of the intracellular bacterial pathogen Listeria monocytogenes is considered nonfunctional. There are no known conditions for DNA transformation, and the Com master activator gene, comK, is interrupted by a temperate prophage. Here, we show that the L. monocytogenes Com system is required during infection to promote bacterial escape from macrophage phagosomes in a manner that is independent of DNA uptake. Further, we find that regulation of the Com system relies on the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
204
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 191 publications
(213 citation statements)
references
References 49 publications
(54 reference statements)
3
204
0
Order By: Relevance
“…Among Gram-positive bacteria, two master regulators control the expression of competence-related genes: the transcription factor ComK (in B. subtilis) (18) and the alternative sigma factor H (in S. pneumoniae [19,20], S. aureus [21], and Lactobacillus sakei [31]). Rabinovich et al reported the presence of a ComK recognition site (the ComK box) upstream of the competence machinery operons (comG, comE, and comF) in L. monocytogenes (16). However, the involvement of H in the expression of these genes has not been explored.…”
Section: Canonicalmentioning
confidence: 99%
See 4 more Smart Citations
“…Among Gram-positive bacteria, two master regulators control the expression of competence-related genes: the transcription factor ComK (in B. subtilis) (18) and the alternative sigma factor H (in S. pneumoniae [19,20], S. aureus [21], and Lactobacillus sakei [31]). Rabinovich et al reported the presence of a ComK recognition site (the ComK box) upstream of the competence machinery operons (comG, comE, and comF) in L. monocytogenes (16). However, the involvement of H in the expression of these genes has not been explored.…”
Section: Canonicalmentioning
confidence: 99%
“…The L. monocytogenes EGDe strain has a prophage-disrupted comK gene. This prophage has been reported to induce the expression of competence machinery genes by its excision from comK during intracellular growth (16). To eliminate the influence of the comK-disrupting phage, we cured the EGDe strain and used this as the wild-type (wt) strain for subsequent strain constructions and comparisons.…”
Section: Canonicalmentioning
confidence: 99%
See 3 more Smart Citations